Características nutricionais e físicas do milho com diferentes texturas e tempos de armazenamento - Santos, Sandro de Castro (2015)
The experiment was carried out from December 2011 to February 2013 at the Federal Institute Goiano (IF Goiano) - Morrinhos. The design was completely randomized in a factorial arrangement 5x4, five treatments (storage times of 0, 60, 120, 180, 240 days) and four types of maize hybrids with different textures (hard, medium-hard, those semi and toothed ). The objective was to evaluate the quality of different types of hybrids stored for a period up to 240 days by temporal variation of the chemical components of the grain, the vitreousness and degradability. The pellets were collected and stored in bags raffia type and subsequently the collection of samples made in accordance with the storage time, and then stored in an oven at 20 ° C. There was a loss of dry matter (P> 0.05) for all hybrids throughout the storage period ranging from 0.43% to 1.43% to hybrid hard for toothed hybrid. Featuring which grain has hard texture corn with improved resistance to storage than the corn grain mealy texture. There was no difference (P> 0.05) among all treatments for the crude protein content. As for vitreousness the average figures for hybrid hard and semi-hard texture were similar (P> 0.05) 79.2% and 77.7%, respectively. And vitreousness grain hybrids for those semi toothed texture and the values did not differ (P> 0.05) were 69.87% and 67.4%, respectively. Thus, one can observe the presence of only two groups: hard grain texture and toothed texture. The toothed grain and semidentados achieved the highest degradation rates (P> 0.05) compared to hard and semi-hard, 68.6%, 68.4%, 73.72% and 72.01%, respectively. The determination of the MS degradability shows that the soft texture of the corn kernels allows greater share of rumen microorganisms in relation to grain hard texture. Thus, the corn produced in Brazil has the advantage of being suitable for storage due to their degree of resistance and more productive than the corn dough. Moreover, the farinaceous grains are more digestible and which has been demonstrated is that this work were not different from in the storage flint hybrids.